Core Java - Horstmann, Cay S., 1959- (Pearson, 2019)
"Core Java" has long been recognized as the leading, no-nonsense tutorial and reference for experienced programmers who want to write robust Java code for real-world applications. Now, Core Java, Volume I Fundamentals, Tenth Edition, has been extensively updated to reflect the most eagerly awaited and innovative version of Java in years: Java SE 8. Rewritten and reorganized to illuminate new Java SE 8 features, idioms, and best practices, it contains hundreds of example programs all carefully crafted for easy understanding and practical applicability. Writing for serious programmers solving real-world problems, Cay Horstmann helps you achieve a deep understanding of the Java language and library. In this first volume of the two-volume work, Horstmann focuses on fundamental language concepts and the foundations of modern user interface programming. You ll find in-depth coverage of topics ranging from Java object-oriented programming to generics, collections, lambda expressions, Swing UI design, and the latest approaches to concurrency and functional programming.--